Organizational values of rural managers in a cooperative system - Teston, Sayonara de Fátima; Zawadzki, Patrick; Verdinelli, Miguel Angel (Revista de Administração da UFSM, 2020)
Purpose: The values can be different according to the sociodemographic profile and motivate rural managers’ behavior. The study aims to survey and compare organizational values with rural property managers’ demographic data in this context. Design/methodology/approach: This is a census of rural soy properties in a cooperative system in the western region of Santa Catarina. For the survey, the study had self-completed questionnaires on values and demographic data. The results were analyzed using descriptive statistics and group comparison tests. Findings: Through the statistical analysis, it was possible to verify significant organizational values differences compared with different age and education groups. Originality/value: The study has mainly an empirical contribution, as the diagnosis made can improve the understanding of the behavior of managers, among them, about the decision-making process and guide people management policies both in the cooperative and rural property.